2011
DOI: 10.1103/physreva.83.053620
|View full text |Cite|
|
Sign up to set email alerts
|

Coherent adiabatic transport of atoms in radio-frequency traps

Abstract: Coherent transport by adiabatic passage has recently been suggested as a high-fidelity technique to engineer the center-of-mass state of single atoms in inhomogeneous environments. While the basic theory behind this process is well understood, several conceptual challenges for its experimental observation have still to be addressed. One of these is the difficulty that currently available optical or magnetic micro-trap systems have in adjusting the tunneling rate time dependently while keeping resonance between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…14). Additionally, as discussed in [89], time-dependent trapping frequencies can be considered to compensate for the time-dependent energy shifts that the non-linear interaction produces in each well. In the context of the three-mode Hamiltonian, the SAP sequence has also been discussed in a cyclic triple well potential [130].…”
Section: Bose-einstein Condensatesmentioning
confidence: 99%
See 1 more Smart Citation
“…14). Additionally, as discussed in [89], time-dependent trapping frequencies can be considered to compensate for the time-dependent energy shifts that the non-linear interaction produces in each well. In the context of the three-mode Hamiltonian, the SAP sequence has also been discussed in a cyclic triple well potential [130].…”
Section: Bose-einstein Condensatesmentioning
confidence: 99%
“…Moving the traps can be achieved by changing the individual rf frequencies that are associated with each trap. An exact sequence that allows to realize the SAP transfer was given in [89], where it was also shown that high transfer fidelities can be achieved without the need for any additional compensation potentials.…”
Section: Radio-frequency Trapsmentioning
confidence: 99%
“…E.g., the signal depends on the position of atoms through the resonance condition for the dressing frequency. In a system with multiple rf fields [3,28,29] the signal gives information about the spatial distribution of the atoms [30]. Methods based on either the Voigt or Faraday effect can be readily implemented in dressed atom experiments to provide low-noise detection with little additional overhead.…”
Section: Introductionmentioning
confidence: 99%
“…A single electron in a TQD can be directly transferred between outer dots by adiabatic passage via a dark state (DS) without ever populating other instantaneous eigenstates of the system . Such techniques, known as coherent transfer by adiabatic passage (CTAP), have been extended to more complicated architectures in solid state devices as well as in cold atoms . Other proposals consider the level detuning as a control parameter to transfer a qubit state .…”
Section: Introductionmentioning
confidence: 99%